ISLAMIC WORK ETHICS AND ENTREPRENEURIAL ORIENTATION TO MICRO BUSINESS' FINANCIAL PERFORMANCE IN MICRO BUSINESS OF MUSLIM FAMILY - Hasbullah, Yudistira; Christiana, Ria Renny; Bernarto, Innocentius; Uno, Sandiaga Salahuddin (Universitas Brawijaya, Indonesia, 2022)
This study focuses on the effect of Islamic Work Ethics (IWE) and Entrepreneurial Orientation (EO) on the Financial Performance (FP) of Muslim-family-owned-micro businesses in Indonesia. The sample was obtained from micro-enterprises registered with OK-OCE (social institutions that function as entrepreneurship centers in various districts). The purposive sampling method is used with the criteria of Muslim family-owned businesses and home industries that produce food and beverages, restaurants, and cafes. Using a SmartPLS software (PLS-SEM method), 246 micro-business data samples were processed and analyzed. The result shows that IWE has a significantly positive influence on EO; secondly, EO has a significantly positive influence on FP; while last, IWE has no significant impact on FP. However, the IWE indirectly positively affects financial performance through EO as the mediating variable. This empirical evidence contributes a novelty in Islamic Work Ethics and entrepreneurship literature, especially in Indonesia. For further research, there are several suggestions, such as using objective financial performance data; using other sectors or industries as the sample, such as the apparel industry; and including a moderating variable such as business regulation, etc.